Anti-reflection composition, anti-reflection film and application of anti-reflection film
By using polymers formed by polycondensation reaction of triazine compounds and diepoxy compounds, combined with other components, an anti-reflective film with high refractive index, low extinction coefficient and excellent etching rate was prepared, which solved the problem of insufficient optical performance of existing isocyanurate compounds and achieved an efficient lithography process.
Patent Information
- Application Number
- CN202411990152.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The application of existing isocyanurate compounds in the field of lithography is limited by poor optical performance, with a low refractive index and a high extinction absorption, making it difficult to meet the needs of high resolution and efficient etching.
A polymer formed by polycondensation reaction of triazine-based compounds and diepoxy-based compounds is used as the main component of the antireflection composition, and an acid-generating agent, a crosslinking agent, a solvent and a surfactant are combined to form an antireflection film with a high refractive index, a low extinction coefficient and an excellent etching rate.
The solvent resistance and etching rate of the anti-reflective film are significantly improved, meeting the needs of high resolution and efficient etching, while maintaining good optical performance.
Smart Images

Figure CN119758666A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of semiconductor processing, and in particular provides an anti-reflection composition and a preparation method and application thereof. Background Art
[0002] In the manufacture of semiconductor devices, micro-machining by photolithography using photoresist (photoresist) compositions is a necessary means to achieve key steps such as accurate etching of circuit patterns and thin film deposition. Micro-machining of semiconductor devices generally refers to forming a photoresist film on a substrate such as a silicon wafer, then irradiating the film with active light such as ultraviolet rays through a mask pattern with a semiconductor device pattern, developing, and etching the silicon wafer with the obtained resist pattern as a protective film. In recent years, with the continuous development of high integration of semiconductor devices, the active light used also has a tendency to shorten from i-line (wavelength 365nm), KrF excimer laser (wavelength 248nm) to ArF excimer laser (wavelength 193nm). At the same time, the diffuse reflection of active light from the substrate and the influence of standing waves have become a big problem. In order to improve the accuracy of photolithography and the resolution of the pattern, the method of setting an anti-reflection film between the photoresist film and the substrate has been widely studied.
[0003] Anti-reflection film refers to a layer of anti-reflection material added between the photoresist and the substrate that can effectively eliminate the interference standing waves formed by light reflection. The anti-reflection film can increase the exposure energy range and focal length, reduce the impact of substrate geometric structure differences on the uniformity of key dimensions, reduce the circular gaps caused by the scattering of reflected light, and alleviate the swing curve effect and concave effect caused by the different thickness of the photoresist due to the substrate configuration. Nowadays, the semiconductor and integrated circuit manufacturing fields are still striving to improve the resolution of photoresist patterns, so higher requirements are placed on the performance of anti-reflection coating compositions.
[0004] Currently, isocyanurate compounds are often used in anti-reflective coating compositions. Although existing isocyanurate compounds have a high anti-reflective effect, their optical properties are poor, that is, the refractive index is low and the extinction absorbance is high, which limits their application in the field of lithography. Summary of the invention
[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide an anti-reflection composition and an anti-reflection film and their application. The anti-reflection film prepared from the anti-reflection composition has solvent resistance, can prevent intermixing with the photoresist layer, and has a high refractive index, a low extinction coefficient and an excellent etching rate.
[0006] In a first aspect, the present invention provides an antireflective composition, comprising a polymer, an acid generator, a crosslinking agent, a solvent and an optional surfactant, wherein the polymer is a product formed by a condensation reaction of a compound A and a compound B, the compound A is a triazine compound as shown in Formula 1, and the compound B is a compound having two epoxy groups.
[0007]
[0008] In Formula 1, L is selected from an alkylene group having 1 to 8 carbon atoms or an arylene group having 6 to 12 carbon atoms. In the anti-reflection composition of the present invention, the polymer used is a condensation product of a triazine substituted with a triamine carboxyl group and a diepoxy compound, and the condensation product includes a main chain structure composed of nitrogen-containing heterocyclic rings (triazine), amine groups and ester groups (-COO-, formed by condensation of epoxy groups and carboxyl groups) and a nitrogen-containing side chain structure formed by amine groups (-NH-). The polymer meeting the structural characteristics can significantly improve the etching rate, and the polymer also has a higher refractive index n and a lower absorbance k. In this way, the polymer is applied to the anti-reflection adhesive, and interacts with components such as a crosslinking agent, a surfactant, and an acid generator to improve the optical properties of the anti-reflection film formed, and improve the solvent resistance and etching rate.
[0009] In a second aspect, the present invention provides an anti-reflection film, wherein the anti-reflection film is formed by coating the anti-reflection composition described in the first aspect of the present invention on a substrate and curing the coating.
[0010] In particular, when ArF excimer laser (wavelength 193 nm) is used in microfabrication of a photolithography process, the antireflection film can efficiently absorb reflected light from a substrate, has a high refractive index and a low extinction coefficient, and has a higher dry etching rate.
[0011] In a third aspect, the present invention provides use of the anti-reflective composition described in the first aspect or the anti-reflective film described in the second aspect in preparing photolithographic patterns.
[0012] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0013] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0014] The "range" disclosed in the present invention is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit. The range defined in this way can be inclusive or exclusive of the end value, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form an undefined range, and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an undefined range.
[0015] If not otherwise specified, all embodiments and optional embodiments of the present invention may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present invention.
[0016] In the present invention, the alkyl group may include a straight chain alkyl group and a branched chain alkyl group, and specific examples of the alkyl group include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, heptyl, n-octyl, 2-ethylhexyl, etc. An alkylene group refers to a divalent group formed by further losing a hydrogen atom of an alkyl group, and the number of carbon atoms of the alkylene group may be 1 to 8, specifically 1, 2, 3, 4, 5, 6, 7 or 8.
[0017] In the present invention, an arylene group refers to a divalent group formed by losing a hydrogen atom from an aryl group, wherein specific examples of the aryl group include phenyl, naphthyl, and biphenyl.
[0018] In the present invention, Further, the non-positioned connecting bonds involved in the ring refer to those extending from the ring system. It means that one end of the connecting bond can be connected to any position in the ring system that the bond passes through, and the other end is connected to the rest of the compound structure. The group shown in formula a below includes any possible connection method shown in formula a-1 to formula a-3:
[0019]
[0020] The first aspect of the present invention provides an antireflective composition, which comprises a polymer, an acid generator, a crosslinking agent, a solvent and an optional surfactant, wherein the polymer is a condensation polymer formed by a condensation reaction of a compound A and a compound B.
[0021] In the present invention, the compound A is a triazine compound having a structure as shown in Formula 1,
[0022]
[0023] In Formula 1, L is selected from an alkylene group having 1 to 8 carbon atoms or an arylene group having 6 to 12 carbon atoms.
[0024] The compound B is a compound having two epoxy groups (diepoxy compound). The epoxy group in the compound B undergoes a ring-opening reaction with the carboxyl group in the compound A in the polycondensation reaction to form an ester group, so as to obtain a polycondensate having triazine, amine (-NH-) and ester (-COO-) in the molecular structure.
[0025] In some embodiments, in Formula 1, L is selected from an alkylene group or a phenylene group having 1 to 5 carbon atoms.
[0026] Specifically, in Formula 1, Selected from any one of the following groups:
[0027]
[0028] Wherein, n is 1, 2, 3, 4 or 5; R is an alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isopropyl, tert-butyl, etc.
[0029] In some embodiments, the compound A is selected from at least one of the following compounds A-1 to A-6:
[0030]
[0031] In the present invention, the compound A can be obtained commercially or synthesized by methods well known in the art, for example, in the presence of a base and a solvent (such as water), cyanuric chloride (TCT) and a compound C (structure: ) was prepared by high temperature reflux or microwave irradiation according to the following synthesis route. The specific synthesis method can be found in the literature: Karuehanon et al. Microwave-assisted S N Ar reaction of 2,4,6-trichloro-1,3,5-triazine for therapid synthesis of C3-symmetrical polycarboxylate ligands[J], Tetrahedron Letters 53(2012)3486–3489.
[0032]
[0033] In some embodiments, the compound B may be selected from diepoxy compounds containing a sulfur atom (S).
[0034] Further, the compound B is selected from at least one of 4,4'-sulfonyl diphenol diglycidyl ether (as shown in formula b-1), 4,4'-bis(glycidyloxy) diphenyl disulfide (as shown in formula b-2) and 1,1'-dioxirane ethyl sulfide (as shown in formula b-3):
[0035]
[0036] In some embodiments, the molar ratio of the compound A to the compound B is (0.8-2.0):1, for example, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.5:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, etc.
[0037] In some embodiments, the conditions of the condensation polymerization reaction include: a temperature of 80 to 100°C, for example, 80°C, 85°C, 90°C, 92°C, 95°C, 98°C, 100°C, etc.; a time of 5 to 10h, for example, 5h, 6h, 7.5h, 8h, 8.5h, 9h, 10h, etc.
[0038] In the present invention, the polycondensation method may include solution polycondensation.
[0039] As some specific embodiments, the polymer can be prepared by a method comprising the following steps:
[0040] (1) Under the protection of an inert gas, in the presence of a catalyst and an organic solvent, subjecting compound A and compound B to a reflux reaction under stirring conditions to form a resin (i.e., a polymer), thereby obtaining a reaction solution containing a polymer;
[0041] (2) diluting the reaction solution with an organic solvent to obtain a reaction dilution solution;
[0042] (3) Under stirring conditions, the reaction dilution solution is dropped into water to disperse and precipitate the polymer, which is then recovered (such as by centrifugal separation), washed and dried to obtain a polymer.
[0043] In step (1), the inert gas is, for example, nitrogen.
[0044] In step (1), the catalyst can be selected from alkaline catalysts commonly used in polycondensation reactions.
[0045] Furthermore, the catalyst is at least one of benzyltriethylammonium chloride, tetrabutylammonium chloride and tetraethylammonium bromide.
[0046] Furthermore, based on the total mass of the compound A and the compound B, the mass dosage of the catalyst is 0.5% to 2%, for example, 0.55%, 0.6%, 0.65%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.5%, 1.7%, 1.8%, etc.
[0047] In step (1) and step (2), the organic solvent used can be selected from various inert solvents. Further, the organic solvent is selected from at least one of propylene glycol monomethyl ether acetate (PGMEA), ethyl lactate, butyl lactate, propylene glycol monomethyl ether and N-methyl pyrrolidone.
[0048] In step (1), the mass ratio of the total mass of the compound A and the compound B to the mass ratio of the organic solvent can be 1:(1.5-3), for example, 1:1.5, 1:1.6, 1:1.8, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.7, etc.
[0049] The mass ratio of the organic solvent in step (2) to the organic solvent in step (1) can be (0.8-1.5):1, for example, 0.8:1, 0.9:1, 1:1, 1.2:1, etc.
[0050] In step (3), the solvent used for washing may be water.
[0051] In step (3), the drying may be vacuum drying.
[0052] In some embodiments, the structure of the polymer includes at least one of the repeating units shown in Formula I to Formula III:
[0053]
[0054] In the repeating unit, the carboxyl group retained in the side chain can improve the solubility of the polymer in the composition. As some examples, the repeating unit can specifically be the following structure:
[0055]
[0056]
[0057] In some embodiments, the weight average molecular weight (M) of the polymer w ) is 1500 to 5000, preferably 2000 to 4500, and the molecular weight distribution index PDI (M w / M n , M n is the number average molecular weight) can be 1.2 to 2.0.
[0058] In the present invention, the molecular weight of the polymer can be measured by gel permeation chromatography (GPC) using polystyrene as a standard sample.
[0059] In some embodiments, based on the total mass of the anti-reflective composition, the mass content of the polymer can be 5% to 15%, for example, 5%, 6%, 7%, 7.5%, 8%, 9%, 9.5%, 9.8%, 9.9%, 10%, 10.2%, 10.5%, 11%, 12%, 13%, 15%, etc.
[0060] In the present invention, the acid generator can be used as a catalyst for the curing reaction, and can be specifically selected from a thermal acid generator and / or a photoacid generator, preferably a thermal acid generator.
[0061] In the present invention, the thermal acid generator can be selected from various sulfonic acid compounds and carboxylic acid compounds. As some examples, the thermal acid generator can be selected from at least one of p-toluenesulfonic acid, trifluoromethanesulfonic acid, pyridinium p-toluenesulfonate, pyridinium phenolsulfonic acid, pyridinium p-hydroxybenzenesulfonate, pyridinium trifluoromethanesulfonic acid, salicylic acid, camphorsulfonic acid, 5-sulfosalicylic acid, 4-chlorobenzenesulfonic acid, 4-hydroxybenzenesulfonic acid, benzene disulfonic acid, 1-naphthalenesulfonic acid, citric acid, benzoic acid and hydroxybenzoic acid.
[0062] In the present invention, the photoacid generator may be selected from various onium salt compounds, sulfonyl imide compounds, and disulfonyl diazomethane compounds.
[0063] As some examples, the onium salt compound can be one or more of diphenyliodonium hexafluorophosphate, diphenyliodonium trifluoromethanesulfonate, diphenyliodonium nonafluoro-n-butanesulfonate, diphenyliodonium perfluoro-n-octanesulfonate, diphenyliodonium camphorsulfonate, bis(4-tert-butylphenyl)iodonium, and bis(4-tert-butylphenyl)iodonium trifluoromethanesulfonate.
[0064] As some examples, the sulfonyl imide compound may be one or more of N-(trifluoromethanesulfonyloxy)succinimide, N-(nonafluoro-n-butanesulfonyloxy)succinimide, N-(camphorsulfonyloxy)succinimide, and N-(trifluoromethanesulfonyloxy)naphthalenimide.
[0065] As some examples, the disulfonyldiazomethane compound may be one or more of bis(trifluoromethylsulfonyl)diazomethane, bis(cyclohexylsulfonyl)diazomethane, bis(phenylsulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, bis(2,4-dimethylbenzenesulfonyl)diazomethane and methylsulfonyl-p-toluenesulfonyldiazomethane.
[0066] In some embodiments, based on the total weight of the anti-reflective composition, the mass content of the acid generator is 0.1% to 5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 0.8%, 0.9%, 1%, 1.2%, 1.5%, 2%, 3%, 3.5%, 4%, 5%, etc.
[0067] In the present invention, the addition of the crosslinking agent can prevent the antireflective film from mixing with the photoresist. Generally, the crosslinking agent can be selected from various substituted urea compounds. According to some embodiments, the crosslinking agent is selected from at least one of 1,3,4,6-tetrakis(butoxymethyl)glycoluril, 1,3,4,6-tetrakis(hydroxymethyl)glycoluril, 1,3-di(hydroxymethyl)urea, 1,1,3,3-tetrakis(butoxymethyl)urea and 1,1,3,3-tetrakis(methoxymethyl)urea.
[0068] In some embodiments, based on the total weight of the anti-reflective composition, the mass content of the crosslinking agent is 1% to 10%, for example, 1%, 2%, 2.5%, 3%, 3.2%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 9%, 10%, etc.
[0069] In the present invention, the antireflective composition may or may not contain a surfactant. According to some embodiments, the surfactant may be a fluorinated surfactant and / or a non-fluorinated surfactant, preferably a non-ionic fluorinated surfactant.
[0070] As some examples, the nonionic fluorinated surfactant can be a perfluorinated C4 surfactant (e.g., FC-4430, FC-4432 surfactants from 3M) or a fluorodiol (e.g., POLYFOX PF-636, PF-6320, PF-656, PF-6520 fluorosurfactants from Omnova).
[0071] In some embodiments, based on the total weight of the anti-reflective composition, the mass content of the surfactant is 0-5%, for example, 0.01%, 0.1%, 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, 0.9%, 1%, 1.2%, 1.5%, 1.7%, 2%, 2.1%, 2.8%, 3%, 3.5%, 4%, 4.5%, etc.
[0072] The present invention does not particularly limit the solvent used in the composition, as long as it can dissolve other components in the composition and make the composition satisfy the solution state. Specific examples of the solvent, but not limited to, include one or more of the following solvents: ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monomethyl ether acetate, propylene glycol propyl ether acetate, toluene, xylene, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, cycloheptanone, 4-methyl-2-pentanol, methyl 2-hydroxyisobutyrate, Ethyl 2-hydroxyisobutyrate, ethyl ethoxylate, 2-hydroxyethyl acetate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl pyruvate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, 2-heptanone, methoxycyclopentane, anisole, γ-butyrolactone, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide.
[0073] In some embodiments, based on the total weight of the anti-reflective composition, the mass content of the solvent is 80% to 90%, for example, 80%, 82%, 82.6%, 83%, 84%, 85%, 86%, 87%, 88%, 90%, etc.
[0074] In the present invention, the polymer, the acid generator, the cross-linking agent and the optional surfactant may be uniformly mixed with the solvent, and optionally filtered to obtain the anti-reflective composition.
[0075] The second aspect of the present invention provides an anti-reflection film, which is formed by coating the anti-reflection composition on a substrate and curing the coating.
[0076] In the present invention, the substrate can be selected from semiconductor substrates used in various photolithography processes, such as silicon wafers, germanium wafers, or compound substrates such as gallium arsenide, indium phosphide, gallium nitride, indium nitride, and aluminum nitride.
[0077] In the present invention, the curing method may include heat treatment, the temperature of the heat treatment may be 100 to 200° C., and the time may be 0.5 to 20 minutes, preferably 0.5 to 10 minutes.
[0078] The anti-reflection film of the present invention has strong absorption for short wavelengths, and can efficiently absorb reflected light from a semiconductor substrate when ArF excimer laser (wavelength 193 nm) is used in microfabrication of a photolithography process, and the anti-reflection film has a high refractive index, a low extinction coefficient, and a high dry etching rate.
[0079] To this end, the third aspect of the present invention provides use of the anti-reflective composition or the anti-reflective film in preparing a photolithography pattern.
[0080] According to the present invention, the application method may include: first coating the anti-reflective composition on a substrate and curing to form the anti-reflective layer; then coating a photoresist composition on the anti-reflective layer to form a photoresist layer, followed by exposure and development.
[0081] In some embodiments, the application further comprises: before the development, baking the exposed photoresist layer to enhance the solubility difference between the exposed and non-exposed regions in the photoresist layer.
[0082] According to the present invention, the developer used in the development may generally be a water-based developer, preferably an alkaline water-based developer.
[0083] Furthermore, the application further comprises: after development, baking the photoresist layer at 100-150° C. for several minutes to harden the developed exposed area.
[0084] Furthermore, the application also includes: etching the area without the photoresist layer on the developed substrate, for example, etching with a hydrofluoric acid etching solution or chemical gas (such as O2, CF4, CHF3, Ar) plasma.
[0085] The following are examples of the present invention. The following examples are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0086] The following synthesis examples are used to illustrate the preparation methods of compound A and polymers used in the examples.
[0087] Synthesis Example 1: Synthesis of Compound A-1
[0088]
[0089] Dissolve m-aminobenzoic acid (0.26 g, 1.94 mmol) and NaOH (0.22 g, 5.40 mmol) in 1 mL of water, and drip the above solution into a 20 mL test tube containing 1 mL of cyanuric chloride (0.1 g, 0.54 mmol) aqueous solution (0°C). Heat the resulting mixture to room temperature, add zeolite, place the test tube on the turntable of a microwave oven (Samsung GB872, 850 W, 2.54 GHz), irradiate at 180 W for 2 min, and irradiate 5 times under this condition, cooling the product in a water bath during each irradiation. After the microwave is turned off, the product is cooled and acidified with concentrated hydrochloric acid, the precipitate is collected by filtration, washed with water and ethanol in turn, and then dried at 80°C to obtain a solid product (Compound A-1) as a white powder. 1H NMR, 13 The results of CNMR characterization of the product are as follows: 1 H NMR (D2O, 400MHz): δ7.24 (t, J = 7.9Hz, 3H), 7.43 (d, J = 7.7Hz, 3H), 7.51 (d, J = 7.9Hz, 3H), 7.74 (s, 3H) ppm; 13 C NMR (DMSO-d6, 100MHz) δ171.6,165.9,138.5,136.8,128.6,124.5,123.8,122.0.
[0090] Synthesis Example 2: Synthesis of Compound A-2
[0091]
[0092] Dissolve valine (0.23 g, 1.94 mmol) and NaOH (0.22 g, 5.40 mmol) in 1 mL of water, and drip the above solution into a 20 mL test tube containing 1 mL of cyanuric chloride (0.1 g, 0.54 mmol) aqueous solution (0°C). Heat the resulting mixture to room temperature, add zeolite, place the test tube on the turntable of a microwave oven (Samsung GB872, 850 W, 2.54 GHz), irradiate at 180 W for 2 min, and irradiate 5 times under this condition, cooling the product in a water bath during each irradiation. After the microwave is turned off, the product is cooled and acidified with concentrated hydrochloric acid, the precipitate is collected by filtration, washed with water and ethanol in turn, and then dried at 80°C to obtain a solid product (Compound A-2) as a white powder. 1 H NMR, 13 The results of C NMR characterization of the product are as follows: 1 H NMR (D2O, 400MHz): δ0.67 (dd, J = 28.6, 6.8, 18H), 1.65-1.70 (m, 3H) 2.82 (dd, J = 5.2Hz, 3H) ppm; 13 CNMR (D2O, 100MHz): δ17.0, 31.8, 61.7, 168.5, 183.1.
[0093] Synthesis Examples 3 to 5
[0094] Compounds A-3 to A-5 were prepared according to the method of Synthesis Example 1, except that m-aminobenzoic acid was replaced by the reactants shown in Table 1, respectively.
[0095] Table 1
[0096]
[0097] Synthesis Example 6: Synthesis of polymer S-1
[0098] At room temperature, 53.50g of compound A-1, 36.24g of 4,4'-sulfonyldiphenol diglycidyl ether, 0.89g of tetrabutylammonium chloride and 210g of propylene glycol monomethyl ether acetate (PGMEA) were added to a 2L three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, the temperature was raised to 90°C, and after the reactants were completely dissolved, the timing was started and the reflux reaction was carried out for 8 hours to form a resin (ie, a polymer). After the reaction was completed, the system was cooled to room temperature, and 210g of PGMEA was added thereto, and stirred evenly to obtain a reaction dilution. The above reaction dilution was added dropwise to 5L of water under high-speed stirring to disperse and precipitate the resin, recover the resin, wash with water, and vacuum dry to obtain a resin product (ie, polymer S-1). Polymer S-1 includes repeating units shown in formula I-1, and GPC test (with polystyrene as the standard sample, the same below) M w =3000, PDI=1.6.
[0099]
[0100] Synthesis Example 7: Synthesis of polymer S-2
[0101] At room temperature, 58.36g of compound A-1, 36.25g of 4,4'-bis(epoxypropoxy)diphenyl disulfide, 0.95g of tetrabutylammonium chloride and 220g of PGMEA were added to a 2L three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, the temperature was raised to 90°C, and after the reactants were completely dissolved, the timing was started and the reflux reaction was performed for 8 hours to form a resin. After the reaction was completed, the system was cooled to room temperature, and 220g of PGMEA was added thereto, and stirred evenly to obtain a reaction dilution. The above reaction dilution was added dropwise to 5L of water under high-speed stirring to disperse and precipitate the resin, recover the resin, wash with water, and vacuum dry to obtain a resin product (i.e., polymer S-2). Polymer S-2 includes the repeating unit shown in formula II-2. After GPC testing, M w =3500, PDI=2.0.
[0102]
[0103] Synthesis Example 8: Synthesis of polymer S-3
[0104] At room temperature, 51.14g of compound A-2, 36.24g of 4,4'-sulfonyl diphenol diglycidyl ether, 0.87g of tetrabutylammonium chloride and 203g of PGMEA were added to a 2L three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, the temperature was raised to 90°C, and after the reactants were completely dissolved, the timing was started and the reflux reaction was carried out for 8.5h to form a resin. After the reaction was completed, the system was cooled to room temperature, and 203g of PGMEA was added thereto, and stirred evenly to obtain a reaction dilution. The above reaction dilution was added dropwise to 5L of water under high-speed stirring to disperse and precipitate the resin, recover the resin, wash with water, and vacuum dry to obtain a resin product (i.e., polymer S-3). Polymer S-3 includes the repeating unit shown in formula I-2. After GPC testing, M w =4135, PDI=1.4.
[0105]
[0106] Synthesis Example 9: Synthesis of polymer S-4
[0107] At room temperature, 51.14g of compound A-2, 14.62g of 1,1'-dioxirane ethyl sulfide, 0.69g of tetrabutylammonium chloride and 160g of PGMEA were added to a 2L three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, the temperature was raised to 90°C, and after the reactants were completely dissolved, the reflux reaction was started for 8 hours to form a resin. After the reaction was completed, the system was cooled to room temperature, and 160g of PGMEA was added thereto, and stirred evenly to obtain a reaction dilution. The above reaction dilution was added dropwise to 5L of water under high-speed stirring to disperse and precipitate the resin, recover the resin, wash with water, and vacuum dry to obtain a resin product (i.e., polymer S-4). Polymer S-4 includes the repeating unit shown in formula III-4. After GPC testing, M w =2890, PDI=1.6.
[0108]
[0109] Synthesis example 10
[0110] The polymer S-5 was synthesized according to the method of Synthesis Example 6, except that the compound A-1 was replaced with an equal molar amount of the compound A-3. The polymer S-5 includes the repeating unit shown in formula I-3, and the M w =3642, PDI=1.2.
[0111]
[0112] Synthesis example 11
[0113] The polymer S-6 was synthesized according to the method of Synthesis Example 7, except that the compound A-1 was replaced with an equal molar amount of the compound A-4. The polymer S-6 includes the repeating unit shown in formula II-2. The GPC test shows that M w =2030, PDI=1.3.
[0114]
[0115] Synthesis example 12
[0116] The polymer S-7 was synthesized according to the method of Synthesis Example 9, except that the compound A-2 was replaced by an equal molar amount of the compound A-5. The polymer S-7 includes the repeating unit shown in formula III-2. The GPC test showed that M w =4326, PDI=1.8.
[0117]
[0118] Comparative Synthesis Example 1
[0119] At room temperature, 37.97g of tris(2-carboxyethyl)isocyanurate (0.11mol), 36.24g of 4,4'-sulfonyldiphenol diglycidyl ether, 0.74g of tetrabutylammonium chloride and 173g of PGMEA were added to a 2L three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, the temperature was raised to 90°C, and after the reactants were completely dissolved, the timing was started and the reflux reaction was carried out for 8h to form a resin, and then the reaction solution was cooled to room temperature, and 173g of PGMEA was added thereto, and stirred evenly to obtain a reaction dilution. The above reaction dilution was added dropwise to 5L of water under high-speed stirring to disperse and precipitate the resin, recover the resin, wash with water, and vacuum dry to obtain a resin product, which was recorded as polymer S-D1. Polymer S-D1 includes the structural unit shown in formula V. After GPC testing, M w =3940, PDI=2.2.
[0120]
[0121] Examples 1 to 7 and Comparative Example 1
[0122] After the polymer, solvent, acid generator, crosslinking agent and surfactant are prepared according to the mass percentage in Table 2, they are added to a clean bottle and shaken until the components are completely dissolved. Then, each sample is filtered through a 0.2 μm polyethylene microporous filter to obtain an anti-reflective composition.
[0123] The solvent is propylene glycol monomethyl ether, the acid generator is p-toluenesulfonic acid, the cross-linking agent is 1,3,4,6-tetrakis (hydroxymethyl) glycoluril, and the surfactant is FC-4430 from 3M Company.
[0124] Table 2
[0125]
[0126] Test Case
[0127] The test examples are used to illustrate the performance of the anti-reflection films formed by the anti-reflection compositions of the above embodiments and comparative examples.
[0128] 1. Preparation of anti-reflective film
[0129] The anti-reflection compositions of Examples 1-7 and Comparative Example 1 were respectively spin-coated on silicon wafers and baked at 200° C. for 60 seconds to form a film with a thickness of Anti-reflection film (film thickness measured by KLA film thickness meter).
[0130] 2. Performance Testing
[0131] 1) Optical properties: A spectroscopic ellipsometer (purchased from Woollman) was used to test the refractive index (n value) and extinction coefficient (k value) of the anti-reflection film at 193 nm.
[0132] 2) Etching rate: The etching rate of the film was tested using a TEL-8500P etching device (purchased from TEL). Etching conditions: CHF3 / CF4 / Ar gas anti-reflective film was used for etching, the processing chamber pressure was 40 Pa, the PF power was 1300 W, the gap was 9 mm, the CHF3 gas flow rate was 30 mL / min, the CF4 gas flow rate was 30 mL / min, the Ar gas flow rate was 100 mL / min, and the etching time was 10 s.
[0133] 3) Solvent resistance: The silicon wafer with the anti-reflection film was soaked in propylene glycol methyl ether acetate (PGMEA) for 5 minutes and then baked at 200°C for 60 seconds. The refractive index (n value), extinction coefficient (k value) and film thickness of the anti-reflection film after soaking in PGMEA were tested. The test results are shown in Table 4.
[0134] The test results of the anti-reflection film before immersion are shown in Table 3, and the test results of the anti-reflection film after immersion are shown in Table 4.
[0135] Table 3
[0136]
[0137] It can be seen from Table 3 that, compared with Comparative Example 1, the anti-reflection films formed by the anti-reflection compositions of Examples 1-7 have a higher refractive index, a lower extinction coefficient, and a higher etching rate.
[0138] Table 4
[0139]
[0140] By comparing the data in Table 3 and Table 4, the refractive index and extinction coefficient of the anti-reflection film prepared by using the anti-reflection composition provided in Comparative Example 1 after being immersed in PGMEA are reduced, and the film thickness is reduced from Down to After the anti-reflection film prepared by using the anti-reflection composition of Examples 1-7 was immersed in PGMEA for 5 minutes, the refractive index and extinction coefficient of the film were almost unchanged, and the thickness of the film did not change significantly. It can be seen that the anti-reflection film prepared by using the anti-reflection film composition of Examples 1-7 has good solvent resistance.
[0141] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. An antireflective composition, characterized in that Comprising a polymer, an acid generator, a cross-linking agent, a solvent and an optional surfactant, wherein the polymer is a condensation polymer formed by a condensation reaction between a compound A and a compound B, the compound A is a triazine compound with a structure as shown in Formula 1, and the compound B is a compound having two epoxy groups; In Formula 1, L is selected from an alkylene group having 1 to 8 carbon atoms or an arylene group having 6 to 12 carbon atoms.
2. The antireflective composition according to claim 1, characterized in that In formula 1, Selected from any one of the following groups: Wherein, n is any integer from 1 to 5, and R is an alkyl group having 1 to 4 carbon atoms; Preferably, the compound A is selected from at least one of the following compounds A-1 to A-6:
3. The antireflective composition according to claim 1 or 2, characterized in that The compound B is at least one selected from 4,4'-sulfonyldiphenol diglycidyl ether, 4,4'-bis(glycidyloxy)diphenyl disulfide and 1,1'-dioxirane ethyl sulfide.
4. The antireflective composition according to any one of claims 1 to 3, characterized in that The molar ratio of the compound A to the compound B is (0.8-2.0):1; Preferably, the conditions of the polycondensation reaction include: temperature of 80 to 100° C., time of 5 to 10 h; Preferably, the polymer is obtained by a process comprising the steps of: (1) under the protection of an inert gas, in the presence of a catalyst and an organic solvent, subjecting the compound A and the compound B to a reflux reaction under stirring conditions to obtain a reaction solution containing a polymer; (2) diluting the reaction solution with an organic solvent to obtain a reaction dilution solution; (3) dropping the reaction dilution into water under stirring conditions to disperse and precipitate the polymer, and recovering, washing and drying to obtain the polymer; Preferably, the catalyst is at least one of benzyltriethylammonium chloride, tetrabutylammonium chloride and tetraethylammonium bromide; based on the total mass of the compound A and the compound B, the mass amount of the catalyst is 0.5% to 2%; Preferably, the organic solvent is selected from at least one of propylene glycol monomethyl ether acetate, ethyl lactate, butyl lactate, propylene glycol monomethyl ether and N-methylpyrrolidone; Preferably, in step (1), the mass ratio of the total mass of the compound A and the compound B to the mass ratio of the organic solvent is 1:(1.5-3); Preferably, the mass ratio of the organic solvent in step (2) to the organic solvent in step (1) is (0.8-1.5):1; Preferably, the drying is vacuum drying; Preferably, the weight average molecular weight of the polymer is 1500 to 5000, and the molecular weight distribution index is 1.2 to 2.0; Preferably, the structure of the polymer comprises at least one of the repeating units shown in Formula I to Formula III:
5. The antireflective composition according to any one of claims 1 to 4, characterized in that The acid generator is a thermal acid generator and / or a photoacid generator, preferably a thermal acid generator; More preferably, the thermal acid generator is selected from at least one of p-toluenesulfonic acid, trifluoromethanesulfonic acid, pyridinium p-toluenesulfonate, pyridinium phenolsulfonic acid, pyridinium p-hydroxybenzenesulfonate, pyridinium trifluoromethanesulfonic acid, salicylic acid, camphorsulfonic acid, 5-sulfosalicylic acid, 4-chlorobenzenesulfonic acid, 4-hydroxybenzenesulfonic acid, benzene disulfonic acid, 1-naphthalenesulfonic acid, citric acid, benzoic acid and hydroxybenzoic acid.
6. The antireflective composition according to any one of claims 1 to 5, characterized in that: The crosslinking agent is at least one selected from 1,3,4,6-tetrakis(butoxymethyl)glycoluril, 1,3,4,6-tetrakis(hydroxymethyl)glycoluril, 1,3-di(hydroxymethyl)urea, 1,1,3,3-tetrakis(butoxymethyl)urea and 1,1,3,3-tetrakis(methoxymethyl)urea.
7. The antireflective composition according to any one of claims 1 to 6, characterized in that The surfactant is a fluorinated surfactant and / or a non-fluorinated surfactant, preferably a non-ionic fluorinated surfactant.
8. The antireflective composition according to any one of claims 1 to 7, characterized in that: Based on the total weight of the anti-reflective composition, the mass content of the polymer is 5% to 15%, the mass content of the acid generator is 0.1% to 5%, the mass content of the cross-linking agent is 1% to 10%, the mass content of the surfactant is 0 to 5%, and the mass content of the solvent is 80% to 90%.
9. An antireflection film, characterized in that: The anti-reflection film is formed by coating the anti-reflection composition according to any one of claims 1 to 8 on a substrate and curing the coating; Preferably, the curing method includes heat treatment, the heat treatment temperature is 100-200° C., and the time is 0.5-20 min.
10. Use of the antireflection composition according to any one of claims 1 to 8 or the antireflection film according to claim 9 in preparing photolithographic patterns.
Citation Information
Patent Citations
Self-crosslinkable isocyanurate polymer, anti-reflection coating composition, and preparation method and pattern forming method of composition
CN113929906A
Anti-reflection coating and preparation method thereof
CN117645810A
Resist underlayer film-forming composition containing copolymer that has triazine ring and sulfur atom in main chain
US20170038687A1
Triazine-polymer-containing composition
WO2015098788A1
Triazine ring-containing polymer and pattern-forming composition
WO2022225020A1